Intracranial-to-central venous pressure gap predicts the responsiveness of intracranial pressure to PEEP in patients with traumatic brain injury: a prospective cohort study - Hong Peng Li; Ying Ni Lin; Zhi Hui Cheng; Wei Qu; Liu Zhang; Qing Yun Li (BMC Neurology, 2020)
Abstract Background Mechanical ventilation (MV) with positive end-expiratory pressure (PEEP) is commonly applied in patients with severe traumatic brain injury (sTBI). However, the individual responsiveness of intracranial pressure (ICP) to PEEP varies. Thus, identifying an indicator detecting ICP responsiveness to PEEP is of great significance. As central venous pressure (CVP) could act as an intermediary to transduce pressure from PEEP to ICP, we developed a new indicator, PICGap, representing the gap between baseline ICP and baseline CVP. The aim of the current study was to explore the relationship between PICGap and ICP responsiveness to PEEP. Methods A total of 112 patients with sTBI undergoing MV were enrolled in this prospective cohort study. ICP, CVP, cerebral perfusion pressure (CPP), static compliance of the respiratory system (Cst), and end-tidal carbon dioxide pressure (PetCO2) were recorded at the initial (3 cmH2O) and adjusted (15 cmH2O) levels of PEEP. PICGap was assessed as baseline ICP - baseline CVP (when PEEP = 3 cmH2O). The patients were classified into the ICP responder and non-responder groups based on whether ICP increment with PEEP adjusted from 3 cmH2O to 15 cmH2O was greater than 20% of baseline ICP. The above parameters were compared between the two groups, and prediction of ICP responsiveness to PEEP adjustment was evaluated by receiver operating characteristic (ROC) curve analysis. Results Compared with the non-responder group, the responder group had lower PICGap (1.63 ± 1.33 versus 6.56 ± 2.46 mmHg; p <  0.001), lower baseline ICP, and higher baseline CVP. ROC curve analysis suggested that PICGap was a stronger predictive indicator of ICP responsiveness to PEEP (AUC = 0.957, 95%CI 0.918–0.996; p <  0.001) compared with baseline ICP and baseline CVP, with favorable sensitivity (95.24, 95%CI 86.91–98.70%) and specificity (87.6, 95%CI 75.76–94.27%), at a cut off value of 2.5 mmHg. Conclusion The impact of PEEP on ICP depends on the gap between baseline ICP and baseline CVP, i.e. PICGap. In addition, PICGap is a potential predictor of ICP responsiveness to PEEP adjustment in patients with sTBI.